Front Cover: Polarization‐Entangled Photon Pairs from Warm Atomic Ensemble with Magnetic Background Noise (Adv. Quantum Technol. 3/2023). Issue 3 (10th March 2023) - Bae, Jinhyuk; Park, Jiho; Yu, Ye Jin; Noh, Heung‐Ryoul; Moon, Han Seb
Abstract : The entangled photon‐pairs (red and blue spheres) are generated from the atomic ensemble in the vapor cell with the environmental magnetic field (curves) such as Earth's magnetic field. The focused pump (red) and coupling (blue) lasers are counter‐propagated in the vapor cell, because of the Doppler‐free two‐photon resonant configuration using the counter‐propagating geometry. More details can be found in article number 2200118 by Han Seb Moon and co‐workers.